1998
DOI: 10.14429/dsj.48.3953
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Boron Combustion in Hot Steam Atmosphere

Abstract: ABSTRACT'lllis paper investigates t11e combustion of magnesium and boron powders in hot steam. A thermochemical analysis reveals theoretical results of such interactions. An experimental investigation demonstrates that stable exotllennic oxidation takes place, resulting in actual combustion at 1100 °c for magnesium atld 800 °c for boron. 'llle reaction generates large qUatltity of gaseous products consisting of ahnost pure hydrogen atld correspondiIlg to about 60 per cent of a complete chemical reaction.metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Second to beryllium is boron, which demonstrates a promising theoretical heat and gas (i.e., hydrogen) release. In practice, it is hard to obtain high combustion efficiency of boron (though Rosenband et al [10] have demonstrated combustion of boron in steam), and in addition boron is a relatively expensive ingredient. Hence, for practical applications, aluminum is commonly considered.…”
Section: Fuelmentioning
confidence: 99%
“…Second to beryllium is boron, which demonstrates a promising theoretical heat and gas (i.e., hydrogen) release. In practice, it is hard to obtain high combustion efficiency of boron (though Rosenband et al [10] have demonstrated combustion of boron in steam), and in addition boron is a relatively expensive ingredient. Hence, for practical applications, aluminum is commonly considered.…”
Section: Fuelmentioning
confidence: 99%
“…The transition from zone 2 to 3 is characterized by a sharp increase in the temperature gradient at T ∼ 710 K, which may be explained by ignition of Mg particles. Indeed, as determined by Rosenband et al (1998), Mg powder ignites in steam flow at ∼ 723 K. The reaction rate for burning particles is much higher than for those before ignition, and is usually limited by external diffusion of the oxidizer (Glassman, 1996). Thus, zone 2 is characterized by relatively slow, kinetic-controlled oxidation of Mg particles by water vapor, while in zone 3, rapid diffusion-controlled combustion of Mg particles occurs.…”
Section: Figmentioning
confidence: 99%
“…With high energy densities, metal powders appear to be good candidates for low-carbon energy carriers, and got more attention these last years [3], [4]. Many aspects of metal combustion were investigated through the years, but large part of these work focused on high temperature systems with particles ignition [5]- [9]. Only few studies [10], [11] aimed to investigate the combustion of metal particles subjected to low heating rates, leading to an exclusively heterogeneous combustion, which could be named "slow combustion" (i.e.…”
Section: Introductionmentioning
confidence: 99%